Evaluation of the antibacterial effects of Ag-Tio2 nanoparticles and optimization of its migration to sturgeon caviar (Beluga) - Anvar, A.; Haghighat Kajavi, S.; Ahari, H.; Sharifan, A.; Motallebi, A.; Kakoolaki, S.; Paidari, S. (2019)
Effect of nano composite films to prolong the shelf life of Iranian beluga caviar was investigated at different concentrations of silver nanoparticles. In this study 38 caviar packs each containing 5 g of caviar were divided into 6 treatments with 3 replicates. The concentrations of 1000, 2000, 3000, 4000, 5000 and 6000 ppm of nanoparticles as well as a nano free pack as control were used. The size of nanoparticles was less than 50 nm in treatments number one to four and was less than 10 nm in treatment number five. Packed samples were inoculated with bacteria and fungi and microbiological tests were performed for each sample after 24 hours. Results of gram test and detecting the gram positive bacteria showed the considerable decreases in Staphylococcus aureus, Escherichia coli, Aspergillus flavus and Penicillium strains. Moreover, there was a considerable decrease in fungi and bacterial growth in 5000 and 6000 ppm nano-silver packages (p<0.05). The amount of silver nanoparticle released into the caviar samples were also measured by titration method and application of titrazol with concentrated sulphuric acid. There was no silver residual in different concentrations of silver nanoparticle packages. These results suggest using silver nanoparticles in accurate concentrations could be considered as one of the main solutions to further inhibit spoilage caused by pathogenic microorganisms, and to extend the shelf life of the valuable food products Published